Primary mediastinal choriocarcinoma masquerading as lung metastasis: a rare disease with a fatal outcome - D., Balakrishnan; S., Suppiah; S., Md Sidek; O., Noriah (Community Health Society Malaysia, 2015)
Background: Most germ cell tumors eg. choriocarcinomas are located in the gonads, however about 2–5% arise from extragonadal regions, such as the mediastinum, retroperitoneum, and central nervous system. Non-gestational choriocarcinoma in mediastinum without a detectable primary in the gonads is termed primary mediastinal choriocarcinoma. Materials and method: Contrast-enhanced whole body computed tomography scan and correlated with tumour markers such as beta human chorionic gonadotropin are used to assess the mediastinal mass. Confirmation of diagnosis was made with image guided biopsy, histopathological examination and special staining. Results: Primary mediastinal choriocarcinoma was confirmed by lack of testicular lesion on ultrasound examination and presence of mediastinal mass with multiple metastatic lesions. Confirmation by CKAE1/AE3 (immunohistochemical study) positive which showed presence of multinucleated epithelial cells. Conclusion: Contrast-enhanced computed tomography is useful tool to diagnose this condition as also provide image guided access for biopsy. In correlation with tumour markers investigation and special immunohistochemical studies can help to clinch the diagnosis.